Infection-Associated Nuclear Degeneration in the Rice Blast Fungus Magnaporthe oryzae Requires Non-Selective Macro-Autophagy - He, Min; Kershaw, Michael J.; Soanes, Darren M.; Xia, Yuxian; Talbot, Nicholas J. (PLOS ONE, 2012)
Background The rice blast fungus Magnaporthe oryzae elaborates a specialized infection structure called an appressorium to breach the rice leaf surface and gain access to plant tissue. Appressorium development is controlled by cell cycle progression, and a single round of nuclear division occurs prior to appressorium formation. Mitosis is always followed by programmed cell death of the spore from which the appressorium develops. Nuclear degeneration in the spore is known to be essential for plant infection, but the precise mechanism by which it occurs is not known. Methodology/Principal Findings In yeast, nuclear breakdown requires a specific form of autophagy, known as piecemeal microautophagy of the nucleus (PMN), and we therefore investigated whether this process occurs in the rice blast fungus. Here, we report that M. oryzae possesses two conserved components of a putative PMN pathway, MoVac8 and MoTsc13, but that both are dispensable for nuclear breakdown during plant infection. MoVAC8 encodes a vacuolar membrane protein and MoTSC13 a peri-nuclear and peripheral ER protein. Conclusions/Significance We show that MoVAC8 is necessary for caffeine resistance, but dispensable for pathogenicity of M. oryzae, while MoTSC13 is involved in cell wall stress responses and is an important virulence determinant. By functional analysis of ΔMoatg1 and ΔMoatg4 mutants, we demonstrate that infection-associated nuclear degeneration in M. oryzae instead occurs by non-selective macroautophagy, which is necessary for rice blast disease.